Suppression of the RAC1/MLK3/p38 Signaling Pathway by β-Elemene Alleviates Sepsis-Associated Encephalopathy in Mice - Pan, Cailong; Si, Yanna; Meng, Qinghai; Jing, Ling; Chen, Lu; Zhang, Yong; Bao, Hongguang (Frontiers in Neuroscience, 2019)
It is still difficult to treat sepsis-associated encephalopathy (SAE) which is a diffuse brain dysfunction caused by sepsis, with excessive activation of microglia as one of the main mechanisms. Ras-related C3 botulinum toxin substrate 1 (RAC1) is proven to be a key molecule in the inflammatory signaling network. By using microglial cell line BV-2 and a mouse model of cecal ligation puncture (CLP), we herein evaluated the effects of β-elemene, an extract of Curcuma zedoaria Rosc., on RAC1 signaling in microglia, as well as the mechanism. β-Elemene decreased the expressions of pro-inflammatory cytokines (tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β) and IL-6) and attenuated translocation of nuclear factor-κB (NF-κB) p65 from the cytosol to the nucleus of BV-2 cells after lipopolysaccharide (LPS) treatment. It also inhibited the activation of RAC1, mixed-lineage protein kinase 3 (MLK3) and p38 mitogen-activated protein kinase (MAPK). The phosphorylation of the RAC1 Ser71 site was increased by β-elemene. Moreover, the learning and memory abilities of CLP mice in the water maze test and fear conditioning test were improved after β-elemene treatment. It reduced the expression of the microglial marker IBA1, significantly increased RAC1 Ser71 phosphorylation, and suppressed RAC1/MLK3/p38 signaling activation and inflammatory response in the hippocampus. In conclusion, β-elemene effectively alleviated SAE in mice and inhibited the RAC1/MLK3/p38 signaling pathway in microglia, probably as a safe and eligible potential candidate for clinical SAE treatment.